Cost Effectiveness of Bariatric Surgical Treatment Methods: A Systematic Review - Zeybek, Dolunay Özlem; Yiğit, Vahit (My University, 2023)
Obesity has become an epidemic today and has become one of the important public health problems. Pharmacological treatment, exercise, cognitive behavioural therapy, medical nutrition and bariatric surgery are used in the treatment of obesity. The aim of this study was to systematically identify and evaluate the national and international literature on the cost-effectiveness of bariatric surgery methods. In this context, a systematic search of electronic databases was conducted. Screening, data extraction, and critical assessment of methodological quality were evaluated according to the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). Incremental cost-effectiveness ratio (ICER) and cost per quality-adjusted life year (QALY) were interpreted using the outcome measure. A total of 448 articles were accessed and the full text of 164 articles was analysed. Within the framework of inclusion and exclusion criteria, 20 articles were included in the study. According to the studies in the literature, bariatric surgery is a low-cost or cost-saving treatment option in the long term. There is limited evidence about the long-term clinical effects and safety of bariatric surgery. Therefore, further studies in this context will significantly contribute to the results of cost-effectiveness studies.
Keywords: Bariatric Surgery; Systematic Review; Cost Effectiveness Analysis